Utilização de esteganografia para ampliar confidencialidade em sistemas RFID - Mezzari, Rafael (2012)
Steganography can be defined as the science that studies ways to hide a message within a communication, hiding its existence. Currently, information security and data security are topics widely discussed and highly relevant to information technology. Issues such as confidentiality and authenticity of a message, as weii as privacy of communication are factors that bring concern for the increasingly growing number of users of systems who exchange many messages, whether for personal or commercial purposes. At the same time, RFID systems are becoming more and more widespread, and that raises the challenge to implement security in RFID systems. One common way to secure the information available on the RFID tags is to use cryptography methods. But visibly encrypted information arouses suspicions and curiosity. Due to this fact, it is desired to increase the confidentiality of the information that belong to a RFID system without attracting unwanted attention, using steganography techniques to this end. At the same time, it is necessary to advance the research in methods that increase security while at the same time avoiding incompatibilities related to the industry standards. In order to achieve this, the present work describes a study regarding the use of steganography techniques in order to increase the confidentiality of the information stored in a RFID system without attracting unwanted attention and without changing the standard machine state.